Moderate Replacement Fertility: Tranquility Dimension Variables of Yogyakarta Special Region, Indonesia in 2023 - Aryati, Seri; Sukamdi, Sukamdi; Listyaningsih, Umi (Universitas Negeri Medan, 2025)
This study examines life tranquility in the context of moderate replacement fertility levels in the Special Region of Yogyakarta (DIY) in 2023. The region's diverse social, cultural, and economic characteristics significantly influence fertility trends and family dynamics. Areas like Sleman and Bantul display higher family proportions, reflecting stable fertility levels, while Yogyakarta City faces challenges in maintaining population growth due to lower fertility rates, influenced by urbanization and economic pressures. This urban-rural divide underscores the complex relationship between fertility patterns and socio-economic factors. Despite increasing birth rates in some areas, challenges persist in understanding fertility behaviors, particularly in relation to access to education, healthcare, and family policies. These factors can either support or hinder efforts to achieve sustainable population growth and well-being. This study explores the connections between moderate fertility rates, life tranquility, and socio-economic influences in DIY. It also examines how education, healthcare access, and family planning policies impact family well-being and fertility decisions. The research aims to provide policy solutions to enhance the quality of life for families across the region. By understanding the socio-economic determinants of fertility trends, this study offers insights into urban-rural differences and informs policy design to address fertility changes and promote stable family dynamics.